PENGARUH TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN, KECAKAPAN MANAJERIAL DAN RISIKO LITIGASI TERHADAP MANAJEMEN LABA DENGAN KUALITAS AUDIT SEBAGAI VARIABEL PEMODERASI (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR DI BEI) - Kirana, Raisa; Hasan, Amir (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
The purpose of this study was to examine influence of the level of disclosure offinancial statements, managerial skills and litigation risk to earnings managementwith audit quality as moderating variables. Earnings management in this study wasmeasured by the Modified Jones Model. The data used in this research is secondarydata derived from the financial statements of companies listed on the IndonesiaStock Exchange in 2011 s.d 2014. By using purposive sampling, this study with 92samples. The data analysis method used was moderated regression analysis. Theresults showed that; 1) the level of disclosure of financial statements effect onearnings management, 2) skills of management effect on earnings management, 3)The risk of litigation has no effect on earnings management, 4) The level ofdisclosure of financial statements and audit quality effect on earnings management,5) Skills managerial quality audit had no effect on earnings management, and 5) therisk of litigation is not the quality of the audit effect on earnings management.Keywords: Level of financial statement disclosure, managerial skills, the risk oflitigation, audit quality